2013
DOI: 10.1371/journal.pone.0060630
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Characterization and Role of cAMP/PKA/CREB in the Basal Transcription of the Mouse ORMDL3 Gene

Abstract: Orosomucoid 1-like 3 (ORMDL3) gene was strongly linked with the development of asthma in genetic association studies, and its expression could be significantly induced by allergen in airway epithelial cells of mice. However, the expression mechanism of ORMDL3 was still unclear. Here we have identified and characterized the mouse ORMDL3 gene promoter. Deletion constructs of the 5′ flanking region were fused to a luciferase reporter gene. After transient transfection in mouse fibroblast cell line NIH3T3, a CRE (−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…None of the ORMDL mRNA levels changed significantly after tetracycline-induction of SPT and transcriptional regulation has only been reported for ORMDL3 (7,8,22,23), making it unlikely that a common transcriptional mechanism can account for the regulation we have observed. One possible explanation for these results is that regulation involves alternative splicing or modulation of translational efficiency.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…None of the ORMDL mRNA levels changed significantly after tetracycline-induction of SPT and transcriptional regulation has only been reported for ORMDL3 (7,8,22,23), making it unlikely that a common transcriptional mechanism can account for the regulation we have observed. One possible explanation for these results is that regulation involves alternative splicing or modulation of translational efficiency.…”
Section: Discussionmentioning
confidence: 56%
“…However, while highly homologous to their yeast counterparts, they lack the major portion of the N-terminal domain of the yeast Orm proteins that is phosphorylated by Ypk1, Ypk2, * This work was supported by Uniformed Services University Grants R071KD and Npr1 and far less is known about the mechanisms by which they regulate SPT activity. Transcriptional regulation of ORMDL3, polymorphisms in which are associated with an increased risk of childhood asthma, has been reported (7,8). In addition, Breslow et al reported that silencing of all three ORMDL mRNAs resulted in increased ceramide levels (2).…”
Section: Regulation Of Serine Palmitoyltransferase (Spt)mentioning
confidence: 99%
“…Wu et al (3) explained ORMDL3 as an orosomucoid 1-like 3 gene. This statement, replicated in several other papers (4)(5)(6)(7)(8)(9)(10), originated from the fact that both the yeast ORM1 gene and human a1-acid glycoprotein (orosomucoid 1) gene share the same name, ORM1. However, the amino acid sequence comparison ( Fig.…”
Section: Ormdl Familymentioning
confidence: 86%
“…Furthermore, overexpression of ORMDL3 has been described in patients with different asthma pathologies (7,13), and enhanced expression of ORMDL3 was induced by Est-1, p300, CREB (43), STAT6 (44) as well as Th2 cytokines (67,91). CREB-induced ORMDL3 expression is involved in the retinoic acid receptor pathway activated by all trans-retinoic acid (ATRA), which is PKA dependent (8). ORMDL3 is also an allergen-inducible gene.…”
Section: The Role Of Ormdls In Immune Response Regulationmentioning
confidence: 99%
“…Zhuang et al characterized the mouse ormdl3 gene promoter region by different approaches, including EMSA. In vitro EMSA assays identifi ed a protein -DNA complex and the complex was supershift when it was incubated with the CREB antibody, validating the CREB-binding site in the ormdl3 promoter region [ 51 ].…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 91%